Student team achievement division model (STAD) in increasing human digestive system learning outcomes - Anggita Dwi Yusvi Putri; Elok Sudibyo (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to implement the STAD learning model to improve student learning outcomes and student responses. The STAD model was applied to 29 Semen Gresik Junior High School students. The research design used was one group pretest-posttest design with data collection methods using a test, questionnaire, and observation methods. The research instruments were learning sheets, pretest questions, and student response questionnaire sheets. The study found an increase in learning outcomes through the calculation of N-Gain with an average value of 0.85 in the high category. Student responses in learning activities using the STAD method showed very positive results, with an average percentage of 92%. The application of the STAD learning method was very good at meetings I and II. Based on the research data analysis, it can be concluded that there is an increase in learning outcomes through the STAD type cooperative learning model in the material of the human digestive system.